Intelligence, Personality and Gains from Cooperation in Repeated Interactions - Eugenio Proto; Aldo Rustichini; Andis Sofianos (Center for Economic Studies and ifo Institute (CESifo), 2016)
Intelligence and personality significantly affect social outcomes of individuals. We study how and why these traits affect the outcome of groups, looking specifically at how these characteristics operate in repeated interactions providing opportunity for profitable cooperation. Our experimental method creates two groups of subjects who are similar but have different levels of certain traits, such as higher or lower levels of intelligence, Conscientiousness and Agreeableness. We find that intelligence has a large and positive long-run effect on cooperative behavior when there is a conflict between short-run gains and long-run losses. Initially similar, cooperation rates for groups with different intelligence levels diverge, declining in groups of lower intelligence, and increasing to reach almost full cooperation levels in groups of higher intelligence. Cooperation levels exhibited by more intelligent subjects are payoff sensitive, and not unconditional. Personality traits have a natural, significant although transitory effect on cooperation rates.
Keywords: C73; C91; C92; 330; repeated prisoner's dilemma; cooperation; intelligence